Six-year incidence and systemic associations of retinopathy in a multi-ethnic Asian population without diabetes. Issue 6 (19th January 2021) - Gupta, Preeti; Lamoureux, Ecosse Luc; Sabanayagam, Charumathi; Tham, Yih-Chung; Tan, Gavin; Cheng, Ching-Yu; Wong, Tien Yin; Cheung, Ning
Abstract : Purpose: We described the 6-year incidence and changes of retinopathy, and their associated risk factors in a multi-ethnic Asian population without diabetes. Methods: We included 4374 participants with non-diabetes from a population-based cohort, the Singapore Epidemiology of Eye Disease Study, with gradable retinal photographs at baseline and 6-year follow-up visit. Retinopathy was assessed according to the modified Airlie House classification system. Results: Over the 6-year period, the cumulative rates were 2.5% (106/4279) for retinopathy incidence, 1.0% (1/95) for retinopathy progression and 68.4% (65/95) for retinopathy regression. In multivariable analysis, higher diastolic blood pressure (DBP) (risk ratio (RR)=1.02; 95% CI: 1.00 to 1.04; per 10 mm Hg increase in DBP) and wider retinal arteriolar calibre (RR=1.36; 95% CI: 1.13 to 1.63; per SD increase in central retinal artery equivalent) were associated with higher risk of incident retinopathy, while higher level of high-density lipoprotein (HDL) was associated with lower risk of incident retinopathy (RR=0.56; 95% CI: 0.32 to 0.99; per mmol/L increase in HDL). Compared with Chinese, Malays were more likely to have retinopathy regression (RR=1.63; 95% CI: 1.20 to 2.22), while overweight (RR=0.47; 95% CI: 0.26 to 0.84) and higher glycosylated haemoglobin (HbA1c) level (RR=0.58; 95% CI: 0.37 to 0.93; per per cent increase in HbA1c) were associated with lower likelihood of retinopathy regression. Conclusion: Risk of developing retinopathy in Asians without diabetes is generally low. However, regression of retinopathy over time is common, suggesting that these retinopathy signs may reflect subclinical reversible microvascular dysfunction. Several metabolic risk factors are associated with incidence or regression of retinopathy, suggesting that good metabolic control may still be important in the management of non-diabetic retinopathy.